Synthesis and Evaluation of the Fungal Activity of New Pyrazole-Carboxamides against Colletotrichum gloeosporioides (2020)
The pyrazole core has been recognized by their biological properties and included in the synthesis of modern agrochemicals. Part of these studies consists of making structural modifications to pesticides for commercial purposes to increase efficacy. In this article, we present the synthesis of four new pyrazol-4-carboxamide 8a-8d derivatives (PCD), through a four-step synthetic protocol, starting with edaravone 1 and primary amines like benzo-fused, aliphatic, and hydrazines, through a process of low environmental impact. Synthesized derivatives were evaluated against one fungal strain of Colletotrichum gloeosporioides BA3, fungus that causes several losses to farmers around the world, through in vitro sensitivity tests. The compound 8c showed better inhibiting behavior against Colletotrichum gloeosporioides BA3, inducing a lag phase of almost 2.77 days. These results were obtained via Gompertz modeling, for the first time reported for biological evaluation of pyrazole-carboxamide derivatives against Colletotrichum gloeosporioides.